Efficacy of Metformin for Benign Thyroid Nodules in Subjects With Insulin Resistance: A Systematic Review and Meta-Analysis - Sui, Miao; Yu, Yuan; Zhang, Huifeng; Di, Hongjie; Liu, Chao; Fan, Yaofu (Frontiers in Endocrinology, 2018)
Background: To evaluate the effect of metformin therapy to decrease benign thyroid nodule volume in subjects with insulin resistance (IR). Method: Before January 31, 2018, we searched the PubMed, Cochrane Library, Embase, Web of Science, Chinese Biomedical Literature Database, National Knowledge Infrastructure, WANFANG and VIP Database, selecting published randomised controlled trials (RCTs) and self-controlled trials for the meta-analysis. Pooled standard mean difference with 95% confidence interval was estimated by fixed- or random-effects model depending on heterogeneity. The risk of bias using the Cochrane Collaboration’s tool was performed to assess the quality of the included RCTs. The quality of self-controlled studies was evaluated using the Methodological index for non-randomized studies (MINORS) method. Results: 7 studies (three RCTs and four prospective self-controlled studies) with 240 patients were considered appropriate for the meta-analysis. The results of the meta-analysis indicated that the volume of thyroid nodule decreased significantly after metformin therapy (SMD -0.62, 95% CI -0.98 ⁓ -0.27). 6 studies reported the changes of the level of TSH. TSH levels decreased significantly after metformin therapy (SMD -0.27, 95% CI -0.47 ⁓ -0.07). The pooled data indicated an increase in FT3 level, and an unchanged FT4 after metformin therapy (FT3, SMD 0.25, 95% CI 0.05 ⁓ 0.45; FT4, SMD -0.07, 95% CI -0.27 ⁓ 0.13). HOMA-IR levels decreased significantly after metformin therapy based on the pooled results of three RCTs and three prospective self-controlled studies (SMD -1.08, 95% CI -1.69 ⁓ -0.47). Conclusion: This meta-analysis demonstrated that metformin was safe and useful in shrinking benign thyroid nodules volume, improving thyroid function and IR. Larger number of high-quality prospective studies still need to be performed.